Optimizing treatment sequencing of chemotherapy for patients with rectal cancer: The KIR randomized phase II trial. (February 2021) - Garant, Aurelie; Kavan, Petr; Martin, André-Guy; Azoulay, Laurent; Vendrely, Véronique; Lavoie, Caroline; Vasilevsky, Carol-Ann; Boutros, Marylise; Faria, Julio; Nguyen, Trung Nghia; Ferland, Emery; Des Groseilliers, Sylvain; et al.
Highlights: This randomized trial explores induction oxaliplatin-based chemotherapy for rectal cancer. It prospectively confirms improved compliance of oxaliplatin-based induction chemotherapy. Outcomes appear highly favorable despite limited patient radiation exposure. Abstract: Background: Randomized studies have shown low compliance to adjuvant chemotherapy in rectal cancer patients receiving preoperative chemotherapy and external beam radiation (CT/EBRT) with total mesorectal excision. We hypothesize that giving neoadjuvant CT before local treatment would improve CT compliance. Methods: Between 2010–2017, 180 patients were randomized (2:1) to either Arm A (AA) with FOLFOX x6 cycles prior to high dose rate brachytherapy (HDRBT) and surgery plus adjuvant FOLFOX x6 cycles, or Arm B (AB), with neoadjuvant HDRBT with surgery and adjuvant FOLFOX x12 cycles. The primary endpoint was CT compliance to ≥85% of full-dose CT for the first six cycles. Secondary endpoints were ypT0N0, five-year disease free survival (DFS), local control and overall survival (OS). Results: Patients were randomized to either AA ( n = 120, median age (MA) 62 years) or AB ( n = 60, MA 63 years). 175/180 patients completed HDRBT as planned (97.2%). In AA, two patients expired during CT; three patients post-randomization received short course EBRT because of progression under CT ( n = 2, AA) or personal preference ( n = 1, AB). ypT0N0 was 31% in AA and 28% in AB ( p = 0.7). CT Compliance was 80% in AA and 53% in AB ( p = 0.0002). Acute G3/G4 toxicity was 35.8% in AA and 27.6% in AB ( p = 0.23). With a median follow-up of 48.5 months (IQR 33–72), the five-year DFS was 72.3% with AA and 68.3% with AB ( p = 0.74), the five-year OS 83.8% for AA and 82.2% for AB ( p = 0.53), and the five-year local recurrence was 6.3% for AA and 5.8% for AB ( p = 0.71). Conclusion: We confirmed improved compliance to neoadjuvant CT in this study. Although there is no statistical difference in ypT0N0 rate, local recurrence, and DFS between the two arms, a trend towards favourable oncological outcomes is observed.